The Contribution of Islamic Law as One of the Sources of National Law in the Formation and Development of Agrarian Law in Indonesia - Naldi Gantika; Asasriwarni Asasriwarni; Ikhwan Ikhwan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The development of National Strategic Projects (NSP) requires a substantial amount of land. However, the land acquisition process in Indonesia often encounters the complexity of legal pluralism, particularly in regions where customary law remains deeply rooted, such as West Sumatra, Jambi, and Riau. In West Sumatra, communal and sacred ulayat rights pose significant challenges to the implementation of land acquisition under Law No. 2 of 2012. Similarly, in Jambi and Riau, various forms of customary land rights remain fundamental to local decision-making, which often diverges from state law. This study examines the dynamics of interaction between state law and customary law in NSP land acquisition through a comparative approach. The findings reveal that disharmony between these two legal systems can trigger agrarian conflicts and social resistance, potentially obstructing development. Nevertheless, legal pluralism also provides opportunities for negotiation, adaptation, and the creation of more inclusive models of legal harmonization. This study emphasizes the importance of participatory and responsive approaches in national agrarian policy to ensure that NSP development proceeds in a just manner while respecting local wisdom.